El impacto de la inteligencia artificial en la transformación del comercio internacional: una revisión bibliográfica - Quincha Risco, Gema Valeria (My University, 2025)
Artificial intelligence (AI) has emerged as one of the most influential technologies in the transformation of international trade. This article presents a literature review aimed at analyzing the main applications of AI in foreign trade, identifying opportunities, limitations, and future trends. The methodology consisted of a systematic review of academic literature and institutional reports published between 2015 and 2025 in databases such as Scopus, Web of Science, and Google Scholar. The findings reveal that AI is being applied in five strategic areas: (i) forecasting import and export trends, (ii) market intelligence based on big data, (iii) decision support systems in international operations, (iv) modernization of ports and customs, and (v) management of regulatory, ethical, and technological challenges. In addition, the literature points to a projection of AI integration with blockchain, IoT, and digital traceability systems, shaping an international trade ecosystem that is increasingly automated and transparent. The review also highlights significant gaps, such as limited empirical evidence from developing countries, a lack of comparative studies between AI and traditional methods, and the absence of homogeneous international regulatory frameworks. These challenges underscore the need for inclusive public policies, international cooperation, and the development of digital skills. In conclusion, AI is consolidating as a central driver in the transformation of international trade, with the potential to redefine global competitiveness and efficiency. However, its real impact will depend on the ability to overcome the current technological, ethical, and regulatory barriers that hinder its equitable adoption.
La inteligencia artificial (IA) se ha posicionado como una de las tecnologías más influyentes en la transformación del comercio internacional. Este artículo presenta una revisión bibliográfica cuyo objetivo es analizar las principales aplicaciones de la IA en el ámbito del comercio exterior, identificando oportunidades, limitaciones y tendencias futuras. La metodología consistió en una revisión sistemática de literatura académica y reportes institucionales publicados entre 2015 y 2025 en bases de datos como Scopus, Web of Science y Google Scholar. Los resultados evidencian que la IA está siendo aplicada en cinco áreas estratégicas: (i) predicción de tendencias de importación y exportación, (ii) inteligencia de mercados basada en big data, (iii) sistemas de apoyo a la toma de decisiones en operaciones internacionales, (iv) modernización de puertos y aduanas, y (v) gestión de desafíos normativos, éticos y tecnológicos. Asimismo, se observa una proyección hacia la integración de IA con blockchain, IoT y sistemas de trazabilidad digital, configurando un ecosistema de comercio internacional más automatizado y transparente. La revisión también identifica vacíos importantes en la literatura, como la limitada evidencia empírica en países en desarrollo, la ausencia de estudios comparativos entre IA y métodos tradicionales, y la falta de marcos regulatorios internacionales homogéneos. Estos desafíos plantean la necesidad de políticas públicas inclusivas, cooperación internacional y capacitación de capital humano. En conclusión, la IA constituye un eje articulador en la transformación del comercio internacional, capaz de redefinir la competitividad y eficiencia global. Sin embargo, su impacto dependerá de la capacidad de superar las brechas tecnológicas, éticas y regulatorias que actualmente limitan su adopción equitativa.
Keywords: INTELIGENCIA ARTIFICIAL; COMERCIO INTERNACIONAL; PUERTO; ADUANA; BIG DATA